Policy Advocacy Workshop Tools for Training Medical Students to Act on Climate Change - Holly Rosencranz; Japhia Ramkumar; Leslie Herzog; Warren Lavey (MedEdPORTAL, 2023)
Introduction Doctors are trusted voices for communities and can influence lawmakers on climate change. Effective climate policy advocacy requires awareness, knowledge, and skills not typically taught in medical schools. Such curriculum additions could help students describe reasons for physicians to engage in climate policy advocacy and compose advocacy presentations. Methods To empower engagement in climate policies and develop advocacy skills, we deployed three 90-minute workshops at three institutions for first-, second-, and fourth-year students. The workshops included background on various climate policies of concern to health care professionals, advocacy guidance, scripts and factsheets from physicians’ meetings illustrating advocacy opportunities for students and physicians, and active learning exercises. The exercises utilized advocacy templates and actual proposed actions on climate change. Students worked in small groups on advocacy presentations’ content and format. Each group shared its work, and facilitators provided feedback. Results Out of 102 participants, 29 completed a survey (28% response rate). Using a Likert scale and narratives, students reported significant improvements in readiness to advocate for legislation or policies to mitigate the health effects of climate change, awareness of advocacy opportunities, and capability to prepare advocacy documents. Discussion Workshops on climate policy advocacy can equip medical students with important perspectives on their responsibilities and opportunities, as well as skills to be effective. The physician's voice is critical to promoting policies related to the health impacts of climate change. Targeted workshops with actual examples and exercises on climate advocacy are feasible and important additions to the curriculum.